Management pedagogy:: The addition in elementary school - Mariela González-López; Fernando Angel-G (Har Press Indonesia, 2024)
It's a study with a qualitative approach through action research. With the aim of teaching addition using the Mariela-Lehren-addieren method to students in 3rd and 4th grade. The Method of teaching addition is from the teaching of the basic skills of mathematical thinking, design and evaluation of the teaching strategy, the concept of number positional value, sign, concept of grouping, regrouping of numbers, the algorithm of addition, the practice of it with numerical exercises and reasoned problems. It is concluded that 18 students out of 21, achieved the learning of addition up to 4 digits with the Mariela-Lehren-addieren method through action research. It's inferred that the problems that arise in the learning of the addition, can be rooted by lack of systematic approach in previous educational cycles of the student, absences, learning problems, teaching models, motivation and school synergy.